The Effect of Interactive Media-Based Role-Playing on Elementary School Students' Social Attitudes and Learning Outcomes - Ni'mah Ni'mah; Rahmawati Rahmawati; Rosleni Babo (Pedagogik Journal of Islamic Elementary School, 2023)
The research aims to analyze the effect of interactive media-based role-playing learning on students' social attitudes and learning outcomes. This study used a Quasi-Experimental Research with a Pretest Posttest Nonequivalent Control Group Design. The study involved 150 fifth-grade students as the population. The sample was randomly selected based on the B accreditation criteria, resulting in two schools selected as the experimental group consisting of 39 students and the control group consisting of 30 students. Data collection techniques used were observation, documentation, and tests. The tests were used to measure students' social attitudes and learning outcomes. The results showed that interactive media-based role-playing learning had a significant effect on students' social attitudes and learning outcomes. Role-playing learning provides students with opportunities to build knowledge, understand and express their ideas.